Hadith #1768 - Sahih al-Bukhari - Ibn Buhaina (Sahih al-Bukhari)
The Prophet, while in the state of Ihram, was cupped at the middle of his head at Liha-Jamal.
Grade: Sahih

Hadith #1150 - Sahih Muslim - Ibn Buhaina (Sahih Muslim)
Anas was asked about the garlic; he stated that the Messenger of Allah (ﷺ) had said: He who eats of this plant (garlic) should not approach us and pray along with us.
Grade: Sahih

Hadith #1544 - Sahih Muslim - Ibn Buhaina (Sahih Muslim)
The dawn prayer had commenced when the Messen- ger of Allah (ﷺ) saw a person observing prayer, whereas the Mu’adhdhin had pronounced the Iqama. Upon this he (the Holy Prophet) remarked: Do you say four (rak’ahs) of Fard in the dawn prayer?
Grade: Sahih

Hadith #2145 - Sahih Muslim - Ibn Buhaina (Sahih Muslim)
I forbade you to visit graves, but you may now visit them; I forbade you to eat the flesh of sacrificial animals after three days, but you way now keep it as along as you feel inclined; and I forbade you nabidh except in a water-skin, you may drink it from all kinds of water-skins, but you must not drink anything intoxicating.
Grade: Sahih

Hadith #2583 - Sahih Muslim - Ibn Buhaina (Sahih Muslim)
A woman came to the Messenger of Allah (ﷺ), and the rest of the hadith is the same, but he said:” Fasting of one month.”
Grade: Sahih

Hadith #4914 - Sahih Muslim - Ibn Buhaina (Sahih Muslim)
Don’t throw pebbles. for Allah’s Messenger (ﷺ) did not like it, or he forbade flinging of pebbles since neither the game is taken thereby, nor an enemy defeated. but it may break a tooth or put out an eye. He, afterwards, again saw him flinging pebbles, and said to him: I inform you that the Messenger of Allah (ﷺ) did not approve or he forbade flinging of pebbles, but if I see you again flinging pebbles. I will not speak with you.
Grade: Sahih